Realism - Relativism - Constructivism : Proceedings of the 38th International Wittgenstein Symposium in Kirchberg - Kanzian, Christian; Kletzl, Sebastian; Mitterer, Josef; Neges, Katharina (Publications of the Austrian Ludwig Wittgenstein Society - New Series ;, 2017)
Publications of the series include the official proceedings of the ALWS-conferences and of their special workshops. Theseries is open also for other high-quality publications, especially on the philosophy of Ludwig Wittgenstein and its influence on contemporary systematic philosophy.